Clinical potential in modern medicine of fibrin glues as drug delivery system - João Paulo Galletti Pilon; Daniela Vieira Buchaim; Abdul Latif Hamzé; Carlos Henrique Bertoni Reis; Getúlio Duarte Júnior; Karina Torres Pomini; Rogério Leone Buchaim (Open Journal of Biological Sciences - Peertechz Publications, 2020)
In an attempt to achieve greater therapeutic efficiency of products, especially in the pharmacological area such as drugs in general, the drug delivery system that controls the distribution of substances through macromolecular carriers has been developed with the primary objective of optimizing their delivery to target locations [1].